Layanan Konseling Kelompok Terhadap Self Confidence - Muhammad Syamsul Arifin; Titin Swastinah; Sitti Ernawati (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2019)
This research is the target to be achieved through a series of research activities. Thus, this study specifically aims to determine the Effect of Group Counseling Services on Self Confidence of Class XI Students of HidayatulMubtadiin Vocational School, SidodadiTempurejo, Academic Year 2018/2019.Based on the results of the study, the results of the analysis showed that the value of rxy obtained was 0.458. This number is greater and the r table is significant at 5% = 0.202 with the number of respondents (N) = 95. This result gives the understanding that the null hypothesis (Ho) reads